Resource Transformation and Survival KEDA as Broker In Ekploitation Gold Mine In Botak Mountain Buru District Maluku Province - Solissa, Marcelino (Journal of Local Government Issues, 2019)
This research entitled "Resource Transformation and Keda Survival as Broker in Exploitation of Gold Mine in Baldy Mountain of Buru Maluku Regency". The research with the title aims to know and analyze the transformation of resources and the survival of Keda as a broker in gold mining activity in bald mountain. This research uses a qualitative research type that prioritizes case studies. Data collection techniques such as observation and interview. The elite theory and brokerage concept is used as a blade analysis in reviewing research results. Data analysis techniques are done quickly in the process of interpretation so that data that has been collected does not experience freezing or even become expired. The results of this study show that Keda transformed from the symbolic-based resources of customs and eucalyptus land to material-based resources (gold) by exploiting the illegal gold of bald mountain. In addition, Keda uses wealth as a key resource for building political networks and able to survive to respond to government policies.keywords: Transformation, Survival, Keda, Eksploitation, Gold Mine